On the issue of fly-back spikes in PWM operated single-phase transformer-less grid-tied inverter - Shahid, Zeeshan; Khan, Sheroz; Ahmed, Musse Mohamud; Alam, A. H. M. Zahirul; Hamida, Belal Ahmed (MAGNT Research Report, 2015)
This paper gives in simulation details the effect of switching sequence generation (PWM) on the ultimate wave-shape of the sinusoidal output produced from a constant voltage assumed to be from solar generation. The circuit, consisting of inductive elements, is associated with the issue of fly-back spikes generation when the circuit is switching circuit. The issue of spike generation is explained through giving theoretical details while it is shown that spikes could be detrimental to having adverse effects on the final wave shape. Then are suggested techniques how spikes are controlled by the use of free-wheeling diodes whereby the spikes are reduced from 500V to 10V. The results of this work could find application in studying the stability of systems used for energy harvesting through distributed generation from solar.